Looking Back : Athletic Hall (Raton Range Raton, New Mexico, 1979)
Article reads : This is a 1907 view of the "Athletic Hall" in Cimarron, a building with an interesting history. Built and owned by Narciso Federici, it also served as the site of a laundry and later became a Methodist meeting hall. victor Grant, Cimarron historian, loaned this old photo to the Range's "Looking Back" series.
Newspaper article and Photograph of Athletic Hall
Mater List Item # 6
File location is in the New Mexico File Cabinets
Keywords: Federici, Narciso; Building Photographs; Athletic Hall -- Cimarron, NM; Methodist; Meeting Halls; Cimarron, New Mexico